Co-digestion of crude glycerin associated with cattle manure in biogas production in the State of Paraná, Brazil - Pazuch, Felix Augusto; Siqueira, Jésse; Friedrich, Leandro; Lenz, Anderson Miguel; Nogueira, Carlos Eduardo Camargo; Souza, Samuel Nelson Melegari de (Acta Scientiarum. Technology, 2017)
The addition of different concentrations of crude glycerin, associated with cattle manure, on the volumetric production of biogas is analyzed. Different concentrations of crude glycerin (2, 4 and 6% m m-1) were added as supplement in anaerobic co-digestion of dairy cattle waste, in laboratory batch biodigesters (3.5 L usable volume). The biodigesters were operated under mesophilic conditions (30ÂºC), with 30-day hydraulic retention time (HRT). Total solids (TS), volatile solids (VS) and chemical oxygen demand (COD) were analyzed to determine the efficiency of the process in the removal of organic matter and its effect on biogas production. The addition of 4% glycerin provided a larger production of biogas, approximately 9.307 mL. The efficiency in COD removal decreased in treatments with glycerin, with highest reduction (68%) in the control treatment. There was a 90 and 118% increase respectively for Gli4 and Gli6% treatments. VS reductions Gly 0, Gly 2, Gly 4 and Gly 6% treatments were 18.17, 61.60, 24.36 and 44.83%, for the respective treatments. Â 